2012
DOI: 10.1029/2012gl053952
|View full text |Cite
|
Sign up to set email alerts
|

Emerging local warming signals in observational data

Abstract: [1] The global average temperature of the Earth has increased, but year-to-year variability in local climates impedes the identification of clear changes in observations and human experience. For a signal to become obvious in data records or in a human lifetime it needs to be greater than the noise of variability and thereby lead to a significant shift in the distribution of temperature. We show that locations with the largest amount of warming may not display a clear shift in temperature distributions if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 23 publications
9
72
0
Order By: Relevance
“…To identify the location where models project statistically significant changes, we analyze the ratio of the mean change to variability; this is accomplished by dividing the mean changes over 20-year time periods by the standard deviation over the current climate (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) and shown in terms of standard deviation units (e.g., Mahlstein et al, 2012;Tebaldi et al, 2011). Previous studies have shown that the spatial and temporal scale used to define these changes can determine whether these signals are statistically significant (Lombardozzi et al, 2014).…”
Section: Model Future Projection Analysismentioning
confidence: 99%
“…To identify the location where models project statistically significant changes, we analyze the ratio of the mean change to variability; this is accomplished by dividing the mean changes over 20-year time periods by the standard deviation over the current climate (1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) and shown in terms of standard deviation units (e.g., Mahlstein et al, 2012;Tebaldi et al, 2011). Previous studies have shown that the spatial and temporal scale used to define these changes can determine whether these signals are statistically significant (Lombardozzi et al, 2014).…”
Section: Model Future Projection Analysismentioning
confidence: 99%
“…Previous studies exploring the concept of emergence have largely focused on physical state variables of the atmosphere and ocean, such as temperature, precipitation and sea level (e.g., Diffenbaugh and Scherer, 2011;Hawkins and Sutton, 2012;Mahlstein et al, 2012;Mora et al, 2013;Lyu et al, 2014). Mora et al (2013), for example argued that the tropics, which hold the worlds greatest diversity of marine species, will exhibit emergence in ocean warming 10 years earlier than any of the other global ocean regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, meaningful adherence to this simple principle can be challenging, and in practice researchers commonly encounter datasets for which uncertainty information is generic, misleading, or absent. Climate data records (CDRs) are not immune to this problem, despite the fact that climatic signals are usually subtle (e.g., Kennedy, 2014;Mahlstein et al, 2012;Flannaghan et al, 2014;Barnett et al, 2005), which adds to the importance of rigorous uncertainty characterization in CDRs (e.g., Immler et al, 2010).…”
Section: Introductionmentioning
confidence: 99%